ANALISIS PERBANDINGAN KINERJA TCP DAN UDP PADA JARINGAN MPLS DAN NON-MPLS DENGAN TUNNELING L2TP/IPSEC BERDASARKAN PROTOKOLROUTING BGP, OSPF DAN RIPv2 - Baiq Alung Septiya Nirmala; Andy Hidayat Jatmika; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
The denser data exchange activities on the internet network, of course, requires speed at the time of data transfer, the accuracy of data reaching the recipient, and data security during the data transfer process. So the development of network technology becomes an important thing to research. The Transmission Control Protocol (TCP) and User Datagram Protocol (UDP) protocols at the transport layer play a role in the data transfer process. In this study, the parameters of Quality of Service (QoS) throughput, delay, and jitter of TCP and UDP on Multiprotocol Label Switching (MPLS) networks will be compared, MPLS combined with Layer 2 Tunneling Protocol/Internet Protocol Security (L2TP/IPSec) and Non-MPLS based on routing protocols Open Shortest Path First (OSPF), Routing Information Protocol version 2 (RIPv2) and Border Gateway Protocol (BGP). This research will be conducted using the Graphical Network Simulator-3 (GNS3) simulator. Based on the research conducted, the throughput value of TCP is better than UDP. While the weight of delay and jitter UDP is better than TCP. TCP is a protocol that prioritizes data to arrive intact from sender to receiver. At the same time, UDP is a protocol that prioritizes speed in sending data packets from sender to receiver. TCP and UDP QoS produced the best value on MPLS networks, followed by MPLS networks with L2TP/IPSec tunneling and Non-MPLS. TCP and UDP on Non-MPLS, MPLS, and MPLS networks with L2TP/IPSec Tunneling have the best QoS values in the RIPv2 routing protocol.Keywords: TCP, UDP, MPLS, L2TP/IPSec, BGP, OSPF, RIPv2, GNS3